Recovery factor and conjugate heat transfer for micro jet impingement - Lupton, Thomas (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2010)
Impinging jets are renowned for achieving high rates of heat transfer over extended periods of time. The bulk of the research to date in this area has focused on relatively large diameter jets. However, the current study investigates micro jets of size less than a millimetre. The novel aspect of this research is that it investigates the significance of the effects of compressibility and conjugate heat transfer resulting from micro impinging jets. The influences of these phenomena on heat transfer resulting from larger diameter jets are generally negligible however these influences are amplified in smaller diameter jets. This study examines temperature distributions and associated recovery factors resulting from the impingement of micro, ambient temperature, air jets onto a 25 μm thick stainless steel foil. Prior to impingement the foil is at ambient temperature. However, the velocities of the impinging jets are sufficiently large enough to cause compressibility effects and consequently the temperatures of the jets are reduced. Impingement of these compressible jets results in non-uniform temperature distributions on the foil. These temperature distributions are recorded using an infrared camera with a spatial resolution of 47.5 μm.
Keywords: Mechanical and Manufacturing Engineering, Ph.D.; Ph.D. Trinity College Dublin